Предмет: Математика,
автор: ЛиДанчо
sin(-п/4)+3cos(-п/3)-tg(п/6)+ctg(п/6)
Ответы
Автор ответа:
0
sin(-π/4)+3.cos(-π/3)-tg(π/6)+cotg(π/6)=
=-sin(π/4)+3.cos(π/3)-tg(π/6)+cotg(π/6)=
=-√2/2+3.1/2-√3/3+√3=-√2/2+3/2+2√3/2=
=(2√3-√2+3)/2
=-sin(π/4)+3.cos(π/3)-tg(π/6)+cotg(π/6)=
=-√2/2+3.1/2-√3/3+√3=-√2/2+3/2+2√3/2=
=(2√3-√2+3)/2
Похожие вопросы
Предмет: Литература,
автор: karaevaarina3
Предмет: Математика,
автор: Аноним
Предмет: География,
автор: sonyamelnychenko6
Предмет: Физика,
автор: LDinaM
Предмет: Математика,
автор: 117ysa1